Effect of adding two types of plant waste in some of the gypsum soil properties and the growth yield of wheat plant (Triticum aestivum L.) - Al Hasnawi, Riad A.; Mohammed, Rafal J.; Jafar, Ameer A.; Hassan, Diaa F. (Journal of Kerbala for Agricultural Sciences, 2018)
The experiment was conducted to investigate the effect of two different types of plant residues in some soil gypsum properties and the growth of wheat plant type 99 (Triticum aestivum L). The soil brought from the holy province of Kerbala/Ein Tameer. the soil put in plastic containers of 10 kgm The soil was treated with two types of plant residues (Corn Cobs Residue, date palm leaves) each type added in three levels (0,25,50) t.h-1 The experiment was three replicates according to the design of the CRD After the experiment, the results were statistically analyzed. The following are shown: Decreases in Electrical conductivity values from 6.4 ds.S-1 to 3.6 and 2.9 ds.S-1 at the addition of 50 t. h-1 Corn Cobs Residue and date palm leaves respectively . As well as the percentage of soluble gypsum with increasing with addition of plant residue and the value of the CEC increased to 23.1 and 22.2 cmol. Kg -1 when adding 50 t. h-1 of Corn Cobs Residue and date palm leaves respectively, also increase the proportion of organic matter. The increase in the addition of plant residues to the improvement of plant characteristics has increased the values (plant height, number of branches, straw weight, yield of 1000 grains) of 40 cm, 3 branches of plant, 32.0 g. -1, 27.2 g. when Do not add plant residues (control treatment) to 59 cm, 5.66 g , 49.6 g, 48.1 g) When adding 50 t. h-1.